Algorytm generowania macierzy danych na podstawie macierzy odległości - Kolenda, Maria (Algorithm of Generating Data Matrices on the Basis of Distance Matrices, 2006)
The paper describes techniques of classification scoring. The basis of a score is determined by a heterogeneity of every cluster and every isolated object in a given classification. A few coefficients has been proposed, which determine various degrees of heterogeneity of clusters and isolated objects. On the basis of these coefficients, four types of classifications have been defined: very good, good, weak but sufficient, and bad classification. The paper also describes how to easily find "the best" classification for hierarchical methods. The proposed coefficients have been commented and compared with different coefficients, such as SCI (Silhouette Coefficient) and average innercluster variation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (16); 2006; nr 1100, s. 176-182